Students’ Writing Ability In Generic Structure Of Procedure Text In SMK Padang - Sani, Rini Dwitya; Asty, Herfyna (Jurnal Pendidikan Nasional, 2021)
This study aims to examine the writing skills of 11th graders at SMK Padang focusing on the generic structure in procedural texts. Seeing the use of 3 elements contained in the generic structure, namely objectives, materials, and steps. This study uses a text document made by students and a checklist document as a research instrument. The researcher took the document of the written procedure text from the eleventh grade. Researchers took documents from class eleven fashion 1, clothing 2, clothing 3, and culinary 3 from a total sample of 114 then researchers used a random sampling technique by taking 15% of the number of children so that the sample analyzed was 17 documents. This research is a qualitative descriptive study. The results of the study found that there were 12 correct documents in the use of 3 generic elements of structure in the procedure text. The 12 documents are complete in the use of objectives, materials, and steps, while there are 5 documents that are incomplete in the use of the 3 elements in the generic structure. The five documents on average have errors in the use of materials, these 5 documents do not contain steps or explanations of what materials are needed in these activities that are in accordance with the objectives of the text. So that the results of the overall writing ability of students on the generic structure are included in the good category because it is guided by the results of students' writing about procedural texts.